From the plains to the mountains. Milan and the control of pass hospitals (14th-15th centuries) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
The contribution presents different case studies that have in common their interaction with Milanese authorities and institutions. The hospital of SS. Nicola and Bernardo of Montegiove, i.e. of Gran San Bernardo, was an organization outside the ecclesiastical jurisdiction of the Milanese archbishop and the territory of the state of Milan, as it was controlled by the Savoy family and the Bishop of Sion. The hospitals in the area of the Tre Valli (Leventina, Blenio and Riviera) in the upper Ticino, a territory that was part of the Milanese diocese and that, during the 15th century, was at the centre of disputes between the Duchy of Milan and the Swiss confederation. These cases show the complex network of relations and powers involved in the control of a hospital located in the mountains. The dynamics that generally made the management of welfare institutions difficult, constantly subject to the attention of civil and ecclesiastical authorities, both local and central, became even more complicated following the process of hospital unification in the mid‐fifteenth century, especially because it went hand in hand with the creation of a state administrative system which, in the case of the territories furthest from the capital, was affected by a situation of instability and conflict.
Keywords: Middle Ages; Hospitals; Mountains; Great St Bernard hospice; Ticino; Dukes of Milan